2022
DOI: 10.1038/s41564-022-01211-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an orally active benzoxaborole prodrug effective in the treatment of Chagas disease in non-human primates

Abstract: Trypanosoma cruzi, the agent of Chagas disease, probably infects tens of millions of people, primarily in Latin America, causing morbidity and mortality. The options for treatment and prevention of Chagas disease are limited and underutilized. Here we describe the discovery of a series of benzoxaborole compounds with nanomolar activity against extra- and intracellular stages of T. cruzi. Leveraging both ongoing drug discovery efforts in related kinetoplastids, and the exceptional models for rapid drug screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…2A and supplemental Table 1)). Multiplex serological screening to assess declines in antibody levels to multiple T. cruzi proteins, an indicator of treatment efficacy in humans [16-19] and non-human primates [20], also showed declining antibody levels in most, but not all animals over this relatively short post-treatment observation period (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2A and supplemental Table 1)). Multiplex serological screening to assess declines in antibody levels to multiple T. cruzi proteins, an indicator of treatment efficacy in humans [16-19] and non-human primates [20], also showed declining antibody levels in most, but not all animals over this relatively short post-treatment observation period (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…The unique mechanisms of action, cytotoxic/cytostatic activities, metabolism and tissue distributions of drugs combine to determine effective treatment regimens. We remain optimistic that shorter treatment courses may be possible using other compounds [20] although amastigote dormancy is likely to negate treatment periods of less than several weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some oxaborole compounds have also been nominated as clinical candidates for the treatment of Chagas disease. For instance, Padilla et al reported that the benzoxaborole prodrug AN15368, which targets the mRNA processing pathway in T. cruzi, was uniformly curative in non-human primates with long-term naturally acquired infections (Padilla et al, 2022). Besides, the oxaborole DNDI-6148 showed high curative rates in mouse models of infection and is currently being evaluated in phase I clinical trials (De Rycker et al, 2022).…”
Section: Introductionmentioning
confidence: 99%